Emergency Department Presentations of Patients with Alcohol Use Disorders in An Australian Regional Health District. Issue 1 (December 2022) - Zhang, Jingxiang; Qian, Siyu; Su, Guoxin; Deng, Chao; Reid, David; Curtis, Kate; Sinclair, Barbara; Yu, Ping
Background : This study aimed to investigate the longitudinal changes in emergency department (ED) presentations incurred by patients with alcohol use disorders. Methods : A retrospective quantitative analysis was conducted on patients' ED presentations between December 2011 and January 2019 in an Australian regional health district. The health district has five EDs serving rural, regional, and metropolitan areas. Patients with alcohol use disorders were divided into two groups for comparison: those who had interactions with the community-based Drug and Alcohol (D&A) services and those who did not. Results : A total of 2, 519 individual patients with alcohol use disorders made 21, 715 ED presentations. Among these patients, 75.4% did not have interactions with the community-based D&A services. Compared with those who had, these patients were older, more likely to be diagnosed with abdominal pain (26.9% vs 12.0%, p < 0.001) and chest pain (16.2% vs 8.6%, p < 0.001), and had longer mean length of ED stay (7 hours and 41.7 minutes vs 6 hours and 25.6 minutes, p < 0.001). For the patients who had interactions with the community-based D&A services, their 28-day re-presentation rates decreased from 55.5% (2013–14) to 45.1% (2017–18); however, were higher than that of those who had no interactions (41.1% to 32.8%). Overall, 21.9%−24.5% of the patients were frequent ED presenters (i.e., ≥4 visits per year). Frequent ED presenters were proportionately higher among the patients who had interactions with the community-based D&A services, consistently over the relevant years. Although patients with alcohol use disorders frequently presented to EDs, their alcohol use disorders were only identified in 8.9% of their presentations. Conclusions : Patients with alcohol use disorders were often unidentified in EDs. Those who did not have interactions with the community-based D&A services were less likely to be diagnosed with alcohol use disorders when presenting to EDs.